FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON-KEUANGAN - Angela, Cynthia; Chandra, Santoso (E-Jurnal Akuntansi TSM, 2023)
One of the considerations for investors to invest is to see the value of the company. The aim of this study is to obtain empirical evidence regarding institutional ownership, managerial ownership, proportion of independent commissioners, board size, existence of female commissioners, board size, audit committee, profitability, and capital structure on firm value as measured using the Tobin's Q formula. The objects of this study are non-financial companies listed on the Indonesia Stock Exchange and meeting other criteria from 2019 to 2021. This study uses a purposive sampling method. Empirical evidence obtained from this study shows that profitability has a positive effect on firm value. In addition, other empirical evidence obtained shows that institutional ownership, managerial ownership, proportion of independent commissioners, board size, existence of female commissioners, board size, audit committee, and capital structure have no effect on firm value.